Synchronization Of Estrus In Black Bengal Does (Bangladesh Journal of Animal Science, 2012)
The present study was undertaken to measure estrus response (%), interval to estrus (hr), duration of estrus and conception rate (%) after synchronization in Black Bengal does. Synchronization of estrus was done by intramuscular injection of synthetic PGF2α as dinoprost®. Two trials were conducted with twenty cyclic fertile adult Black Bengal does. The age and body weight of the does were between 18 to 21 months and 11-13 kg, respectively. After synchronization all the does were observed closely up to 48 hours to note the estrus behavior. All the signs or behavior of synchronized estrus were recorded in details. Out of 20 does, 19 does showed behavioral signs of heat and expressed estrus behavior after synchronizing with synthetic PGF2α as dinoprost® injection. The behavioral estrus was found after 45.5 hours and 45 hours injected with 2 ml and 1 ml dinoprost®, respectively. The duration of estrus was recorded 51 hours and 23 hours for does treated with 2 ml and 1 ml dinoprost®, respectively. The conception rate was observed 42.86% and 40.00% treated with 2 ml and 1 ml, respectively. From the result of this study it can be concluded that synchronization of estrus with 1 ml of dinoprost®, may be used for inducing estrus of Black Bengal doe under Bangladesh condition. DOI: http://dx.doi.org/10.3329/bjas.v38i1-2.9907 BJAS 2009; 38(1-2): 7-14